Thermal modelling and simulations of lithium-ion battery systems - Wang, Tao (2016)
Much attention has been paid on lithium-ion batteries recent years because of their wide applications in portable electronic devices as well as in vehicles, ships and aircrafts. However, lithium-ion battery has problems of poor safety characteristics caused by high heat generation and the temperature rise during charge and discharge. High temperature affects the performance, reliability and lifespan of the battery and may cause serious safety hazards such as thermal runaway, even ignition. Therefore, the investigation and thermal management of lithium-ion battery are critical issues in research field.